2018
DOI: 10.1002/jlb.ma1217-484r
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α restricts dengue virus-induced neuropathy

Abstract: Proinflammatory TNF-α facilitates dengue virus (DENV) infection in endovascular dysfunction and neurotoxicity. The introduction of TNF-α blocking therapy with Abs is performed to test its therapeutic effect in this study. In DENV-infected mice, TNF-α production in the brain accompanied the progression of neurotoxicity and encephalitis. DENV infection caused the loss of hippocampal neurons with TNF-α expression around damaged regions, and immunostaining showed the induction of apoptosis in hippocampal neurons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Generally, TNF-α, as well as IL-4, IL-6, IL-8, and IL-10, are increased in dengue patients (Butthep et al, 2012). We previously demonstrated that DENV infection causes overt TNF-α production during the progression of viral encephalitis (Jhan et al, 2018). The cross-talk between aberrant cytokines/chemokines and immune cells in the CNS needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, TNF-α, as well as IL-4, IL-6, IL-8, and IL-10, are increased in dengue patients (Butthep et al, 2012). We previously demonstrated that DENV infection causes overt TNF-α production during the progression of viral encephalitis (Jhan et al, 2018). The cross-talk between aberrant cytokines/chemokines and immune cells in the CNS needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the animal model as in previous studies (Tsai et al, 2016 ; Ho et al, 2017 ; Jhan et al, 2018 ; Kao et al, 2018 ; Shen et al, 2019 ), we inoculated 7-d-old ICR suckling mice (BioLASCO, Taiwan) with 2.5 × 10 5 and 7.5 × 10 5 plaque-forming units (pfu) of DENV 2 (PL046) by simultaneous intracerebral and intraperitoneal injections, respectively. The survival rate and disease score of the mice were monitored daily and recorded.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6J hTNF +++ , IFNα/βR −/− Tg, Tg HLA-A*02:01, and B10.Tg HLA-DR3 C57BL/6J transgenic mice overexpressing human tumor necrosis factor (TNF) and infected with DENV, developed neurological symptoms, and treatment with anti TNF-antibodies reduce mortality suggesting that intervention of this pathway may be used to treat DENV encephalitis [86]. However, when infected iv, these mice do not develop viremia and mount a specific T-cell response against a high virulent DENV strain obtained in the lab.…”
Section: Transgenic Non-humanized Model Of Denvmentioning
confidence: 99%
“…As for recent advances in DENV‐targeted therapy, there has been some promise in mouse models using a combination of sunitinib, a VEGF receptor tyrosine kinase inhibitor, and TNF inhibitors for the reduction in vascular leak and protection from lethal disease . TNF inhibition has also been useful in limiting DENV‐induced encephalitis in mouse models . IVIG has been successfully used to halt capillary leak and hemodynamic instability in a renal transplant patient .…”
Section: Dengue Virusmentioning
confidence: 99%